Institutional deficit, representation, and decentralized forest mangement in Cameroon: elements of natural resource sociology for social theory and public policy - Oyono, P.R. (World Resources Institute and CIFOR, 2004)
Conducted in the East, South, and Northwest Provinces, this study aims to provide an explanation and understanding of the organizational and institutional infrastructure of decentralized management of Cameroon’s forest—also referred to as “local forest management”—and the mechanisms of the transfer of powers and responsibilities to decentralized entities. It shows that in Cameroon’s forestry domain, the institutional arrangements necessary for local management of common pool resources are either nonexistent or insufficient, hence the notion of “deficit.” The study demonstrates that the Cameroonian model of decentralization of forest management is, in the end, an interrupted process, blocked mid-way to fruition by forces on the regional level (mid-level actors) and by a village elite. The findings give rise to a theory of deviation and of a pattern of regional “capture” of forestry localism and decentralized management. The central State, having failed to establish regulation mechanisms and an approach to monitor the process in all its length seems to have been caught short, leaving decentralization in the hands of networks and mid-level actors whose primary interest is financial gain. This shift permits the diversion of forest governance and the setup of legal “gangsterism” in a field where corruption and abuse of power was already deeply entrenched. This study also enumerates different forms of instrumentalization of decentralized management of Cameroon’s forests, as well as the indicators of socio-economic and ecological counter-performance linked to current social and institutional arrangements.